Analyzing decision-making in blockchain governance - Schädler, Lukas; Lustenberger, Michael; Spychiger, Florian (Frontiers in Blockchain, 2023)
Blockchain systems are a novel technology that allow for innovative business models. However, due to the decentralized nature of blockchains, new organizational challenges arise. Blockchains require intricate governance mechanisms to align all interests of the involved stakeholders. A crucial part of blockchain governance is decision-making, i.e., the way how a community of a blockchain system can reach decisions. While blockchain governance has received considerable interest of academia, decision-making in blockchains has not yet been sufficiently addressed. Through an exploratory multiple case study, we establish a framework for analyzing decision-making in blockchain systems and identify two dimensions along which decision-making in blockchains can be classified – namely community-driven vs. institution-driven as well as off-chain vs. on-chain decision-making. Even though blockchains are decentralized systems, we can show that there are often highly centralized elements present. The degree of this centralization varies across blockchains and might be connected to the business cases and origins of the different systems. Furthermore, many factors of decision-making processes in blockchains are still off-chain and only some factors are truly on-chain. We arrived at these insights through a structured approach for decision-making in blockchains. Thus, we provide new tools for researcher and practitioners and pave the way to novel blockchain applications with sound decision-making mechanisms.